1979
DOI: 10.1111/j.1432-1033.1979.tb13118.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Single‐Stranded DNA Isolated from Cultured Muscular Cells during Differentiation and the Transcription of Messenger RNA

Abstract: Single-stranded DNA (ssDNA), equivalent to about 2 "/, of the total nuclear DNA, was isolated by an improved method of hydroxyapatite chromatography from native nuclear DNA of rat myoblast cells and myotubes, of the Lg line. Small quantities of '251-labelled ssDNA were annealed with a large excess of unlabelled DNA, cytoplasmic RNA and mRNA from myoblasts or myotubes. The results indicated that ssDNA belongs to the non-repetitious portion of the cell genome and is formed of two distinct molecular fractions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It has been suggested that DNA demethylation of silenced genes cannot occur without histone acetylation-induced transcription (D’Alessio et al 2007). Transcription leads to a transient formation of single-stranded DNA (Leibovitch & Harel 1978, Leibovitch et al 1979) and it has been hypothesized that transcription may be needed for AID targeting (Chaudhuri et al 2003, Shen et al 2009). When overexpressed in NIH 3T3 cells, AID more efficiently edits a GFP reporter gene transcribed at higher levels, suggesting that transcription may stimulate its activity (Yoshikawa et al 2002).…”
Section: How Is Site-specific Activity Of Deaminases Achieved?mentioning
confidence: 99%
“…It has been suggested that DNA demethylation of silenced genes cannot occur without histone acetylation-induced transcription (D’Alessio et al 2007). Transcription leads to a transient formation of single-stranded DNA (Leibovitch & Harel 1978, Leibovitch et al 1979) and it has been hypothesized that transcription may be needed for AID targeting (Chaudhuri et al 2003, Shen et al 2009). When overexpressed in NIH 3T3 cells, AID more efficiently edits a GFP reporter gene transcribed at higher levels, suggesting that transcription may stimulate its activity (Yoshikawa et al 2002).…”
Section: How Is Site-specific Activity Of Deaminases Achieved?mentioning
confidence: 99%